Suspicion - Hitchcock, Alfred, 1899-1980; Grant, Cary, 1904-1986; Fontaine, Joan, 1917-2013; Hardwicke, Cedric, 1893-1964; Bruce, Nigel, 1895-1953; Whitty, May, Dame, 1865-1948 (Turner Entertainment, 1941)
Μία πλούσια γυναίκα υποψιάζεται πως ο πλειμπόι σύζυγός της είναι δολοφόνος και πως εκείνη είναι το επόμενο θύμα του.